STRATEGI DINAS KOPERASI DAN UMKM DALAM PEMBERDAYAAN USAHA MIKRO, KECIL DAN MENENGAH DI KOTA PEKANBARU - Astuti, Afni; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the strategy of the Department of Cooperatives and MSME and to determine the factors that hinder the strategy of the Department of Cooperatives and MSME in empowering micro, small and medium enterprises in Pekanbaru City. This research is descriptive, describing the reality correctly regarding the strategy of the Department of Cooperatives and MSME in empowering micro, small and medium enterprises in the city of Pekanbaru. Qualitative research aims to reveal certain social situations by describing the true reality. The results of this study are the strategy of the Department of Cooperatives and MSME in empowering micro, small and medium enterprises in the city of Pekanbaru which is applied by the Department of Cooperatives and MSME is strategy formulation, strategy implementation, and strategy evaluation. In the formulation of this strategy, the Cooperatives and MSME Office has not yet maximized the formulation of new strategic initiatives, the formulation of strategies tends to be almost the same as the previous period. The implementation of the strategy has not yet been carried out as planned. Strategy evaluation of the lack of ability of the Pekanbaru City Cooperatives and MSME Office in implementing the strategic initiatives that have been formulated. The factors that hinder the strategy of the Department of Cooperatives and MSME in empowering micro, small and medium enterprises in Pekanbaru City are the limited amount of business capital, limited human resources, limited access to capital. Keywords: Strategy, Empowerment, MSME